Thymol, a dietary monoterpene phenol abrogates mitochondrial dysfunction in β-adrenergic agonist induced myocardial infarcted rats by inhibiting oxidative stress. (25th January 2016) - Nagoor Meeran, M.F.; Jagadeesh, G.S.; Selvaraj, P.
Abstract: Mitochondrial dysfunction has been suggested to be one of the important pathological events in isoproterenol (ISO), a synthetic catecholamine and β-adrenergic agonist induced myocardial infarction (MI). In this context, we have evaluated the impact of thymol against ISO induced oxidative stress and calcium uniporter malfunction involved in the pathology of mitochondrial dysfunction in rats. Male albino Wistar rats were pre and co-treated with thymol (7.5 mg/kg body weight) daily for 7 days. Isoproterenol (100 mg/kg body weight) was subcutaneously injected into rats on 6th and 7th day to induce MI. To explore the extent of cardiac mitochondrial damage, the activities/levels of cardiac marker enzymes, mitochondrial lipid peroxidation products, antioxidants, lipids, calcium, adenosine triphosphate and multi marker enzymes were evaluated. Isoproterenol induced myocardial infarcted rats showed a significant increase in the activities of cardiac diagnostic markers, heart mitochondrial lipid peroxidation, lipids, calcium, and a significant decrease in the activities/levels of heart mitochondrial superoxide dismutase, catalase, glutathione peroxidase, reduced glutathione, isocitrate, malate, α-ketoglutarate and NADH-dehydrogenases, cytochrome-C-oxidase, and adenosine triphosphate. Thymol pre and co-treatment showed near normalized effects on all the biochemical parameters studied. Transmission electron microscopic findings and mitochondrial swelling studies confirmed our biochemical findings. The in vitro study also revealed the potent free-radical scavenging activity of thymol. Thus, thymol attenuates the involvement of ISO against oxidative stress and calcium uniporter malfunction associated with mitochondrial dysfunction in rats. Highlights: Isoproterenol triggers the activation of β-adrenergic receptor. β-adrenergic receptor activation stimulates oxidative stress. Calcium uniporter malfunction plays a crucial role in myocardial infarction. Altered calcium homeostasis results in mitochondrial dysfunction. Thymol counters oxidative stress and altered calcium homeostasis.